Neurofibromatose tipo 1: sobre o que não se vê e o que se sente - uma travessia entre a invisibilidade social e o conhecimento sobre a doença - Alessandra Craig Cerello (2011)
The Neurofibromatosis type 1 (NF1) is a genetic autosomal dominat disease, that has unpredictable manifestation and course, and occurs in approximately 1:2500 births. Although the most common symptoms have benign clinical features, somatic, aesthetic, and psychosocial aspects interfere in patient's daily life. Among these symptoms are the most common changes of: pigmentation (café-au-lait spots, ephelides and Lisch nodules), benign tumors of the central or peripheral nervous tissues called neurofibromas (cutaneous, subcutaneous or plexiform), and bone dysplasia. Besides the most common symptoms, other situations are often associated with NF1, including hyperactivity and learning difficulties. This study aimed to investigate the psychosocial aspects involved in NF1, based on qualitative methodology: the Theory of Social Representations and Social Practices. Fortynine patients with NF1 participated were intervied with through broad format collect, 33 women and 16 men. With 29 of them, the in-depth colletc form were used, for better description of the meaning of the answers. Data treatment was done by qualitative analysis of responses. The answers were organized into units and categories of meanings. The results showed that the level of information about the disease was articulated with almost every category, relating them to the "Unfamiliarity with the disease", especially, but also to "Information about the disease." The hights number of responses was related to the unit "Personal Reactions" to the disease, revealing individualized "Coping" strategies aimed at hiding the symptoms, emotional control, focus on the positive and the change in perspective. Other personal reactions as- "Normal/ Natural", "Negative Feelings" and "Treatment" - that with the meaning of actions for the removal of neurofibromas- had high relevance. We also found high frequency of responses about experiences of stigmatization and prejudice, and low number of referrals to support networks for coping with the disease. This demonstrated that NF1 is a disease marked by social invisibility, reinforcing patients' necessity to develop individual coping strategies. Other categories occoured less frequently, such as "Characterizations and Perceptions regarding Social Aspects" and Characterizations and Perceptions regarding physical / Biological Aspects" in addition to categories that have not formed units, for example"Attribution of Causes" and "Diagnosis." Understanding these exploratory data aims to further the understanding of the NF1 and the experiences associated with it, from a social psychology approach applied to Health